Histopathological Features of the Development of Intestine and Mesenteric Lymph Node Injury in a Nonhuman Primate Model of Partial-body Irradiation with Minimal Bone Marrow Sparing. Issue 3 (March 2019) - Parker, George A.; Li, Na; Takayama, Kyle; Booth, Catherine; Tudor, Gregory L.; Farese, Ann M.; MacVittie, Thomas J.
Abstract : Abstract: Male rhesus macaques were subjected to partial-body irradiation at 10, 11, or 12 Gy with 5% bone marrow protection. Animals were euthanized when dictated by prospectively determined clinical parameters or at approximately 180 d following irradiation. Histological sections of jejunum, colon, and mesenteric lymph node were stained with hematoxylin and eosin as well as a battery of histochemical and immunohistochemical stains. The immediate postirradiation histopathological alterations in the jejunum and colon were based primarily on injury to rapidly proliferating crypt epithelial cells, though there was evidence of additional radiation-induced fibrogenic responses. There was substantial resolution of the radiation-related mucosal injury through the observation period, but microscopically visible defects in mucosal structure persisted to the end of the observation period. In the later stages of the observation period, the jejunum and colon had overt fibrosis that was most commonly located in the submucosa and serosa, with less microscopically discernible involvement of the mucosa. Mesenteric lymph nodes had an immediate postirradiation reduction in cellularity due to the known effects of irradiation on lymphoid cell populations. In later stages of the observation period the lymph nodes also developed fibrotic changes, possibly related to transmigration of immunomodulatory cells and/or signaling molecules from the radiation-damaged intestine.